2004
DOI: 10.1097/01.asn.0000128219.65330.ea
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulosclerosis and Tubulointerstitial Fibrosis are Attenuated with 17β-Estradiol in the Aging Dahl Salt Sensitive Rat

Abstract: Abstract. This study examined the effects of estrogen deficiency by ovariectomy (OVX) and 17␤-estradiol (E 2 ) replacement (OVXϩE 2 ) on glomerulosclerosis and tubulointerstitial fibrosis and the mechanisms contributing to these changes, including expression of collagen type IV and laminin, transforming growth factor-␤ (TGF-␤), and activity of matrix metalloproteinases (MMP) in the kidneys of young (4 mo [4M]) and aged (12 mo [12M]) Dahl salt-sensitive (DSS) rats maintained on a low-salt (0.1% NaCl) diet. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(150 citation statements)
references
References 46 publications
10
137
1
2
Order By: Relevance
“…171 Accordingly, transdermal administration of 17β-estradiol has been shown to effectively reduce salt sensitivity in postmenopausal women. 172 These observations are further supported by preclinical work of Maric et al 173 using ovariectomized Dahl rats as an animal model of postmenopausal salt-sensitive hypertension. In these animals, 17β-estradiol attenuates age-related renal dysfunction.…”
Section: Estrogens and The Kidney: Salt Sensitivity And Renal Diseasesupporting
confidence: 71%
“…171 Accordingly, transdermal administration of 17β-estradiol has been shown to effectively reduce salt sensitivity in postmenopausal women. 172 These observations are further supported by preclinical work of Maric et al 173 using ovariectomized Dahl rats as an animal model of postmenopausal salt-sensitive hypertension. In these animals, 17β-estradiol attenuates age-related renal dysfunction.…”
Section: Estrogens and The Kidney: Salt Sensitivity And Renal Diseasesupporting
confidence: 71%
“…However, modifications of sex hormone status, such as estrogen deficiency induced by ovariectomy, are shown to worsen renal damage and accelerate the progression of renal disease in several models of kidney disease. [42][43][44][45][46] Studies using 17b-estradiol, 2-hydroxyestradiol, or estriol replacement provide evidence that estrogen or estrogen metabolites have a beneficial effect ameliorating renal damage. [43][44][45][46][47][48] For example, the data showed that estrogen or estrogen metabolites reduced albuminuria, attenuated renal lesions, and prevented disease progression in a wide variety of experimental models of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…49 The favorable effects of estrogens in the kidney are possibly related to their known effects on mesangial cells, as demonstrated both in vitro and in vivo, by reducing proliferation 50 and synthesis of collagen and other ECM components, 43,47,51,52 which contributes to preventing the development of glomerulosclerosis [42][43][44][45][46][47] and tubulointerstitial fibrosis. [43][44][45]48 In addition, estrogens induce a reduction in PAI-1 levels. 50 The estrogen-like antifibrotic effects are possibly related to the reduction in TGF-b expression.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol is associated with protective cardio-renal effects in many animal models of hypertension (67,68,70) and the deleterious effects of ovariectomy such as induced hypertension, renal injury, or endothelial dysfunction are reversed with estradiol therapy (70,71). Therefore, the cardio-renal protective effect of estradiol appears to be complex and includes a wide range of regulatory systems.…”
Section: Role Of Estrogenmentioning
confidence: 99%